Integrin-β6 Serves as a Potential Prognostic Serum Biomarker for Gastric Cancer - Li, Zequn; Sun, Yuqi; Xu, Jianfei; Yang, Hao; Liu, Xiaodong; Tian, Yulong; Cao, Shougen; Zhou, Yanbing (Frontiers in Oncology, 2021)
Discovering novel biomarkers that easily accessed is a key step towards the personalized medicine approach for gastric cancer patients. Integrin-β6 (ITGB6) is a subtype of integrin that is exclusively expressed on the surface of epithelial cells and is up-regulated in various tumors. In the present study, a retrospective cohort with 135 gastric cancer patients and a prospective cohort with 34 gastric cancer patients were constructed, ITGB6 expression were detected in both the serum specimens and the tissue specimens. Detailed clinicopathological parameters as well as patients’ survival were recorded. A nomogram including ITGB6 expression was also constructed and validated to predict the prognosis of gastric cancer patients. Results showed that serum ITGB6 expression was obviously increased and associated with tumor stage in gastric cancer patients, serum ITGB6 expression was relatively high in patients with liver metastasis. High ITGB6 expression indicated a poor prognosis, and nomogram including serum ITGB6 expression could predict the prognosis of gastric cancer patients effectively. Moreover, serum ITGB6 expression was associated with ITGB6 expression in tumor tissues. Furthermore, combined serum ITGB6 and CEA levels contributed to the risk stratification and prognostic prediction for gastric cancer patients. In addition, the serum expression of ITGB6 decreased significantly after radical surgery, and a new rise in serum ITGB6 expression indicated tumor recurrence or progression. The present study identified a novel serum biomarker for the risk stratification, prognostic prediction and surveillance of gastric cancer patients.